LITERASI DASAR SEBAGAI FONDASI MULTILITERASI DI ERA DIGITAL - Sri Wahyuni; Rika Jufriazia Manita (Pustabiblia: Journal of Library and Information Science, 2025)
The development of digital technology has expanded the meaning of literacy from merely reading and writing skills into a more complex competence encompassing digital, media, and information literacy. The main problem addressed in this study is how basic literacy supports multiliteracy skills in the digital era, and how the integration among various literacy types can shape critical and creative thinking capacities in facing modern information flows. This research aims to analyze the strategic role of basic literacy as the foundation for multiliteracy development and to examine its integration within Indonesia’s educational and literacy culture context. The method used is library research with a conceptual analysis of 30 recent national and international scholarly sources. The findings indicate that basic literacy plays a central role in developing effective multiliteracy, serving as the basis for critical, logical, and ethical reasoning in processing digital information. The integration of basic, media, technological, and visual literacy forms an adaptive multiliteracy framework suited for contemporary challenges. It is concluded that reading and writing literacy is not merely an initial learning stage but a strategic pillar sustaining all forms of modern literacy. The study recommends that strengthening basic literacy should become a national policy priority and be integrated into educational curricula to prepare Indonesian society to engage critically, creatively, and responsibly in the digital age.